PENERAPAN APLIKASI MoKAS DAN P2UKS TERHADAP PENCEGAHAN DAN PENGENDALIAN INFEKSI DI SEKOLAH DEPOK - Serri Hutahaean; Nourmayansa Vidya Anggraini; Ruth M Bunga Wadu (Jurnal Bakti Masyarakat Indonesia, 2022)
School-age children are an age group that is susceptible to disease, especially the incidence of infection. The problems found in SD X Sawangan, Depok, were conveyed that students often experience symptoms related to infections such as coughs, colds, and diarrhea which can harm children, in addition to health it also has an impact on children's learning backward because they cannot participate in learning at school. The purpose of this activity is to make efforts to prevent and control infection by using the School Children's Health Mobile Application (MoKAS) and to increase the role of school health efforts (P2UKS). This activity is held in August 2022. This activity is carried out for 5th-grade elementary school children who are in charge of UKS at the elementary school Holy Faithful Obedient Depok. The method of implementing this activity is socialization and counseling about infection prevention and control efforts as well as good UKS management in supporting the improvement of health services in schools, conducting training on how to check children's health when using the MoKAS Application, and assisting the UKS Responsible Person using the MoKAS Application. The results of this activity illustrate a change in student knowledge before and after socialization, counseling, and demonstrations so that students who have good knowledge about Covid-19 prevention have increased from 75% to 96.7%. Most students have good infection prevention and control skills with a total of 29 students (96.66%), the ability to carry out a good student health check with a total of 26 students (86.66%), the ability to use the application of MoKAS in infection prevention and control. good with the number of 28 students (93.33%). This activity suggests that schools continue to support infection prevention and control efforts using the MoKAS application and increase the role of school health efforts in supporting the improvement of the health of school residents. ABSTRAK: Anak usia sekolah merupakan kelompok umur yang rawan terjadi penyakit, terutama kejadian infeksi. Masalah yang ditemukan di SD X Sawangan depok disampaikan bahwa siswa sering mengalami gejala yang berhubungan dengan infeksi seperti batuk, pilek, dan diare yang dapat merugikan anak, selain dalam kesehatannya, juga berdampak pada ketertinggalan dalam pembelajaran di sekolah karena tidak bisa mengikuti pembelajaran di sekolah. Tujuan PKM ini adalah melakukan upaya pencegahan dan pengendalian infeksi (PPI) dengan penggunaan Aplikasi Mobile Kesehatan Anak Sekolah (MoKAS) dan peningkatan peran usaha Kesehatan sekolah (P2UKS).  Kegiatan ini dilakukan pada Bulan Agustus 2022. Kegiatan ini dilakukan pada anak kelas 5 di SD Holy Faithful Obedient Depok. Metode pelaksanaan kegiatan ini adalah sosialisasi dan penyuluhan tentang upaya PPI serta manajemen UKS yang baik dalam mendukung peningkatan pelayanan kesehatan di Sekolah, melakukan pelatihan cara memeriksa kesehatan anak sekaligus menggunakan Aplikasi MoKAS, serta pendampingan Penanggung jawab UKS dalam Penggunaan Aplikasi MoKAS. Hasil PKM ini menggambarkan adanya perubahan pada pengetahuan siswa saat sebelum dan sesudah dilakukannya sosialisasi, penyuluhan serta demonstrasi dengan hasil siswa yang memiliki pengetahuan baik terhadap PPI memiliki peningkatan sebesar 75% menjadi 96,7%. Mayoritas siswa memiliki kemampuan melakukan PPI yang baik dengan jumlah 29 siswa (96,66%), Kemampuan melakukan pemeriksaan kesehatan siswa yang baik dengan jumlah 26 siswa (86,66%), kemampuan menggunakan Aplikasi MoKAS dalam PPI yang baik dengan jumlah 28 siswa (93,33%). Kegiatan ini menyarankan supaya sekolah tetap mendukung upaya PPI menggunakan aplikasi MoKAS dan meningkatkan peran usaha Kesehatan sekolah dalam mendukung peningkatan Kesehatan warga sekolah